1989
DOI: 10.2331/suisan.55.859
|View full text |Cite
|
Sign up to set email alerts
|

Requirement of larval red seabream Pagrus major for essential fatty acids.

Abstract: Feeding experiments of the n-3 highly unsaturated fatty acid (n-3 HUFA) requirement on larval red seabream were conducted three times using rotifers enriched by the direct method, which showed a direct relationship between the n-3 HUFA concentration in emulsified lipids and the level on n-3 HUFA in rotifers. Various emulsions containing different levels of n-3 HUFA were pre pared by mixing methyl oleate with pollock and cuttlefish liver oils or a methyl ester mixture con taining 85% of n-3 HUFA and fed to roti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
88
0
8

Year Published

1999
1999
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 168 publications
(102 citation statements)
references
References 4 publications
6
88
0
8
Order By: Relevance
“…This confirms former studies which suggest that in addition to the dietary level of essential fatty acids, the molecular form in which they are present in the diet is also important for good growth and survival of marine fish larvae (Izquierdo, 1988;Izquierdo et al, 1989).…”
Section: Phospholipidssupporting
confidence: 79%
See 3 more Smart Citations
“…This confirms former studies which suggest that in addition to the dietary level of essential fatty acids, the molecular form in which they are present in the diet is also important for good growth and survival of marine fish larvae (Izquierdo, 1988;Izquierdo et al, 1989).…”
Section: Phospholipidssupporting
confidence: 79%
“…Si bien el crecimiento larval durante la etapa de nutrición endó-gena está influenciado por una serie de parámetros abióticos (Watanabe y Kiron, 1994), algunos autores han sugerido que las reservas nutritivas del saco de vitelo aportan los requerimientos necesarios para pasar esta etapa crítica del desarrollo y que el patrón de nutrientes usado por los embriones y larvas recién eclosionadas pueden indicar las necesidades nutricionales de las larvas durante su primera alimentación (Vázquez et al, 1994). Los principales ácidos grasos en los lípidos de huevos en peces marinos tales como el fletán (Hippoglossus hippoglossus) (FalkPetersen et al,1989), rodaballo (Scophthalmus maximus) (Rainuzzo et al, 1993), dorada japonesa (Pagrus major) (Izquierdo et al, 1989a) y dorada (Sparus aurata) (Mourente y Odriozola, 1990) son el DHA, el ácido palmitíco, EPA y el ácido oléico. Se debe indicar que la importancia relativa de cada ácido graso puede diferir entre las especies estudiadas y entre diferentes puestas de huevos de la misma especie.…”
Section: Requerimientos Nutricionales En Larvas De Pecesunclassified
See 2 more Smart Citations
“…Fish oil offers a range of fatty acid classes, mainly contains the long chain n-3 HUFA and thus was considered more superior than maize oil in fish feed [5] . Experiments conducted using live prey [30,31] or a compound diet [32] have shown that the optimal level of n-3 HUFA in diet for marine fish larvae is around 3% (dry matter). The present experiment was designed to have 2.87% and 6.12% (dry matter) n-3 HUFA in the maize oil diet and fish oil diet respectively, when fish were fed fish meal and protein hydrolysate based diets for 32 days, the fish oil did not improve the fish performance (WG, SGR and survival).…”
Section: Discussionmentioning
confidence: 99%